The Synergy of Skill and Reward: Unveiling the Impact of Competence and Compensation on Employee Performance - Haryoto, Cecep Yoto (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this study is to find out and analyze: (1) Compensation (2) Competence; (3) Employee Performance and (3) Effect of Compensation and Competence on employee performance in the Marketing Division of PT Coca Cola Amatil Indonesia, both simultaneously and partially. The research method used in this research is descriptive survey and explanatory survey. The unit of analysis in this study was employees in the Marketing Division of PT Coca Cola Amatil Indonesia with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the compensation received by employees at the Marketing Division of PT Coca Cola Amatil Indonesia in general was relatively adequate, Competence of the Marketing Division Employees of PT Coca Cola Amatil Indonesia was appropriate and sufficient to meet the needs, Employee Performance at the Marketing Division of PT Coca Cola Amatil Indonesia is high, and Compensation and Competence simultaneously influence the Performance of Employees in the Marketing Division of PT Coca Cola Amatil Indonesia. But partially, compensation affects employee performance dominantly rather than competency. Because compensation dominantly affects performance, it is the first priority in improving employee performance. Therefore the Marketing Division of PT Coca Cola Amatil Indonesia is advised to be given compensation in accordance with the provisions by increasing other benefits, so that they are able to work more professionally.